Description of verb morphology in colloquial Bangla (BRAC University Journal, 2026)
The paper presents a description of the Colloquial Bangla (Bengali) verb morphology in relation to the Standard Bangla. As researchers begin to conduct studies in various aspects of Bangla, e.g. in computational linguistics or child language acquisition, descriptions of colloquial Bangla are required. An important area of enquiry is the verb inflectional system in the Colloquial Bangla (CB) which is significantly different from the Standard Bangla (SB) with regard to the forms of the grammatical markers. The paper discusses the implications of these differences.